Bank Credit and Fintech Credit: The Moderating Role of Institutional Quality - Nguyen, Liem; Bui, Phuong; Nguyen, Tran Thai Ha; Wong, Wing-Keung (Asian Academy of Management Journal of Accounting and Finance, 2025)
Lending is a primary activity for banks, and the introduction and growth of fintech credit create a new landscape in the competition setting in this field. Previous research focuses on the effect of fintech credit provision on bank credit and bank performance, but not the reverse direction. Meanwhile, theoretically it can be expected that bank credit can affect the growth of fintech credit. This study employs a country-level dataset from 2013 to 2019 to fill the gaps mentioned. We find that bank credit tends to exert a complementary effect on fintech credit. This result implies that the two types of credit suppliers do not aim at the same target customers and tend to cooperate for their mutual benefits, and the growth of bank credit generally facilitates fintech credit. However, when a country has better institutional quality, bank credit negatively affects fintech credit, emphasizing on the substitution effect. The study offers some implications for relevant stakeholders based on the research findings.